Loss of function of MusaPUB genes in banana can provide enhanced resistance to bacterial wilt disease - Tripathi, L.; Ntui, V.O.; Muiruri, S.; Shah, T.; Tripathi, J.N. (2025)
Plants deploy a sophisticated defense mechanism against pathogens through pattern recognition receptors (PRRs) and resistance (R) proteins, activating pattern-triggered immunity (PTI) and effector-triggered immunity (ETI). E3 ubiquitin ligases, notably U-box types like PUB22 and PUB23, modulate PTI by suppressing immune responses. The role of MusaPUB22/23 in immunity against Xanthomonas vasicola pv. musacearum (Xvm), the cause of banana Xanthomonas wilt (BXW) in East Africa, was investigated by knocking out these genes in the BXW-susceptible ‘Sukali Ndiizi’ cultivar. The gene targets used in this study, MusaPUB22 and MusaPUB23, were identified through prior comparative transcriptomics analysis, which revealed their upregulation in susceptible versus resistant genotypes during early infection with Xvm. Gene edited plants exhibited mutations in both genes, with no significant growth penalties in most events. Several edited lines displayed complete resistance to Xvm infection, while others showed partial resistance, in contrast to the full susceptibility of wild-type controls. Resistance correlated with hydrogen peroxide accumulation and activation of key defense-related genes, indicating enhanced immune responses. This study identifies MusaPUB22/23 as susceptibility genes and provides strong evidence for their role in modulating immunity in banana. The results highlight the potential of gene editing as a promising strategy against BXW, addressing a crucial agricultural issue in East Africa while unraveling plant immunity regulation and paving the way for disease-resistant crop engineering targeting PUB genes.